1992
DOI: 10.1159/000186738
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Intestinal Permeability Measured by Differently Sized Polyethylene Glycols in Acute Uremic Rats

Abstract: The effect of experimental acute renal failure on the intestinal permeability measured by differently sized polyethylene glycols (PEG) was studied in rats. The permeability was assessed by analysing the 24-hour urinary recovery of PEG molecules (size 326-1,162 D). Acute renal failure was induced by clamping the left renal artery and right-sided nephrectomy. The overall urinary recovery of PEG was decreased in the uremic rats. However, the relative recovery of larger molecules (range 590-1,162 D) was further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The absorption rate and the amount of ciprofloxacin absorbed via the gut have never been investigated for rats suffering from RF. However, Magnusson et al (13) evidenced that in rats, chronic RF induces changes in intestinal mucosa that lead to an increased intestinal permeability towards polar drugs via an increased water absorption. The increase in ciprofloxacin K a is Mean Ϯ SD (median) for pharmacokinetic parameter b : a In each group, the number of control rats was seven and the number of rats with RF was seven.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption rate and the amount of ciprofloxacin absorbed via the gut have never been investigated for rats suffering from RF. However, Magnusson et al (13) evidenced that in rats, chronic RF induces changes in intestinal mucosa that lead to an increased intestinal permeability towards polar drugs via an increased water absorption. The increase in ciprofloxacin K a is Mean Ϯ SD (median) for pharmacokinetic parameter b : a In each group, the number of control rats was seven and the number of rats with RF was seven.…”
Section: Discussionmentioning
confidence: 99%
“…Magnusson et al . reported that intestinal permeability was increased in chronic uremic rat while it was decreased in acute cases 150,151 . They also noted that a low protein diet decreased the hyperpermeability in chronic cases.…”
Section: Intestinal Barrier Dysfunction and Diseasesmentioning
confidence: 93%
“…Neutrophil activation and dysfunction are probably caused by endotoxemia 14 , a well-recognized phenomenon in ESRD. Bacterial translocation across an impaired gastrointestinal barrier might be a source for endotoxin 15 16 17 18 19 20 . Gut stunning may explain such a disruption of the gut-mucosal barrier 21 .…”
mentioning
confidence: 99%